Initial biological evaluations of a novel microtubule‐based PET ligand in Alzheimer's disease. (December 2021) - Damuka, Naresh; Orr, Miranda E.; Macauley, Shannon L.; Shively, Carol A.; Lockhart, Samuel N.; Bansode, Avinash; Kim, Jeongchul; Frye, Brett M.; Register, Thomas C.; Mintz, Akiva; Whitlow, Christopher T.; Craft, Suzanne; et al.
Abstract: Background: Microtubule (MT) integrity is critical for cell function and viability. Abnormal MT‐stability in AD is commonly attributed to hyperphosphorylation of the MT‐associated protein, tau. However, the time course of MT instability in disease progression remains unknown. In vivo MT imaging offers an opportunity to gain critical information on MT changes in relation to staging of ADRDs. Our lab reported the first brain‐penetrant MT PET ligand, [ 11 C]MPC‐6827 and evaluated in vivo imaging in normal rodents and non‐human primates (NHP). Herein we report its initial biological evaluations in (a) neuronal cells, (b) tau knock‐out mice, and (c) aged NHPs (Caribbean‐origin vervets) with changes in AD‐related biomarkers. Method: In vitro [ 11 C]MPC‐6827 cell uptake assay was performed in patient‐derived SH‐SY5Y cells with different MT destabilizing and stabilizing agents. Radioactive binding efficiency was determined as %ID (injected dose)/mg of protein present in each well. Dynamic 0‐60 min brain microPET/CT imaging was performed in tau knock‐out and wild type mice (n=4). Four vervets (20‐29y) with different cerebrospinal fluid (CSF) Aβ42 levels (2 high levels‐1461, 1614 and 2 low levels‐579, 732) underwent 0‐120 min brain PET/CT imaging with [ 11 C]MPC‐6827. ROIs were drawn on the whole‐brain and SUVR values were calculated from co‐registered PET/MR images. Result: In vitro cell uptake assays with [ 11 C]MPC‐6827 in SH‐SY5Y cells displayed high uptake with MT destabilizing agents and low uptake with stabilizing agents. MicroPET imaging demonstrated higher radioactive brain uptake in tau knockout over wild‐type mice. Vervets with low CSF Aβ42 levels showed high radioactive brain uptake and the youngest vervet (20y) displayed lowest brain uptake. Conclusion: Consistent with our in vitro cell uptake and in vivo rodent imaging experiments, [ 11 C]MPC‐6827 increased with MT destabilizations. Radioactive uptake was inversely related to CSF Aβ levels and directly related to age in a NHP model of AD (Fig 1). Collectively our data suggest that [ 11 C]MPC‐6827 is more selective towards destabilized MTs. On‐going experiments include rigorous PET imaging analyses, determination of metabolic plasma‐blood parameters, and correlations with Aβ42 and tau levels. Nonetheless, our promising results support the high translational utility of [ 11 C]MPC‐6827 to image MTs in ADRDs.